Fine mapping of the autosomal dominant juvenile open angle glaucoma (GLC1A) region and evaluation of candidate genes. - Sunden, S L; Alward, W L; Nichols, B E; Rokhlina, T R; Nystuen, A; Stone, E M; Sheffield, V C

(untitled) (Genome Research, 1996)
Juvenile Open Angle Glaucoma (GLC1A) is an autosomal optic neuropathy that has been localized previously to chromosome 1q. Here we report the fine mapping of the disease region using YACs and a high density of polymorphic microsatellite markers. This study utilized two large JOAG pedigrees genotyped at 36 loci from chromosome 1q21-q31 to refine the GLC1A locus to a approximately 3-cM region flanked by YAC-derived microsatellite markers D1S3665 and D1S3664. The candidate genes LAMC1, NPR1, and CNR2 were excluded from the region by linkage. Four other genes, SELE, SELL, TXGP1, and APT1LG1, were determined to lie within the critical region through YAC content and linkage mapping. The YAC-STS content map of the critical region provides the groundwork for the construction of a transcription map and the identification of the disease-causing gene.